2018
DOI: 10.1021/acsomega.8b02933
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of SF6 Decomposed Products over ZnO(101̅0): Effects of O and Zn Vacancies

Abstract: We carried out a density functional theory study to investigate the adsorption behavior of four kinds of SF 6 decomposed products over the ZnO(101̅0) surface. The effects of O and Zn vacancies on the surface were also considered. For perfect ZnO(101̅0) surface, the adsorption of SO 2 and H 2 S exhibits stronger chemical interactions compared to the adsorption of SOF 2 and SO 2 F 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The order of k values of different ZnO/melamine ratios was 0.0263 min −1 (1.2:1) > 0.0169 min −1 (0.8:1) > 0.0079 min −1 ~0.0065 min −1 (0.6:1, 1.0:1, 1.4:1). It is known that ZnO with more non-polar (100) planes could exhibit better photocatalytic properties [ 11 , 22 ]. XRD analyses demonstrated that the oriented growth of ZnO rods in ZnO-X varied according to different ZnO/melamine ratios ( Figure 1 and Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The order of k values of different ZnO/melamine ratios was 0.0263 min −1 (1.2:1) > 0.0169 min −1 (0.8:1) > 0.0079 min −1 ~0.0065 min −1 (0.6:1, 1.0:1, 1.4:1). It is known that ZnO with more non-polar (100) planes could exhibit better photocatalytic properties [ 11 , 22 ]. XRD analyses demonstrated that the oriented growth of ZnO rods in ZnO-X varied according to different ZnO/melamine ratios ( Figure 1 and Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been reported that ZnO with non-polar planes could exhibit higher stability and properties. For example, ZnO with non-polar (100) planes showed higher gas-sensing properties compared to that with polar (001) planes [ 11 ]. Therefore, the performance of ZnO is expected to improve by combining defect engineering with orientation growth.…”
Section: Introductionmentioning
confidence: 99%
“…The formation energy of vacancy defects is defined by the following formula Here, E V Fe /V S –FeS and E FeS denote the total energy of the FeS(001) model containing V Fe /V S and the perfect surface, respectively. The μ i represents the atomic chemical potential introduced by the formation of V Fe /V S .…”
Section: Methodsmentioning
confidence: 99%
“…Traditional adsorption materials such as molecular sieves, metal oxides, and carbon materials have low efficiency in capturing SF 6 applications due to problems such as low specific surface area and poor adsorption selectivity [4]. In recent years, metal-organic frameworks (MOFs) not only have high specific surface area but also have dense and homogeneous microporous distribution, making them good gas storage material [5][6][7]. ZIFs are a class of zeolitic imidazole skeletons in MOFs made by the coordination of organic ligands with metal ions [8][9][10], where ZIF-67 has metal Co as the metal center cross-linked with organic imidazole esters to form a polyhedral skeleton structure [11][12][13].…”
Section: Introductionmentioning
confidence: 99%